Modelling the barriers of Lean Six Sigma for Indian micro-small medium enterprises: An ISM and MICMAC approach. Issue 5 (10th October 2019) - Singh, Mahipal; Kumar, Pankaj; Rathi, Rajeev
Abstract : Purpose: The purpose of this paper is to investigate the barriers of Lean Six Sigma (LSS) and develop the interrelationship among them using interpretive structural modelling (ISM) and Matriced Impact Croises Multiplication Appliquee a un Classement (MICMAC). Design/methodology/approach: Using systematic literature review and expert's opinions, 26 LSS barriers have been extracted and finalized through statistical analysis, that is importance-index analysis and corrected item minus total correlation methods. The statistical analysis of purified 22 LSS barriers has been carried out and consistency of finalized barriers has been checked through reliability statistical test in Statistical Package for the Social Sciences software. Finally, the contextual relationship among finalized LSS barriers is developed using ISM and MICMAC approach. Findings: The ISM model indicates that insufficient management commitment and involvement, lack of resources, lack of training and education, lack of strategic thinking, lack of training funds are strategic factors; improper project selection, poor selection of employee for belt training, lack of total employee involvement, lack of awareness of about LSS are prudent factors; unclear vision, high implementation cost, resistance to culture change, weak supplier linkage, poor alignment between company's goal and customer demand are burst factors. Furthermore, MICMAC analysis is splitting the LSSBs in four clusters according to their driving power and dependency. These results provide a clear mind-set to engineering manager for focusing more on LSS barriers according to their driving power and dependency. Research limitations/implications: There may be biasness in making pairwise comparison matrix of barriers due to involvement of expert's opinion as human error. Practical implications: The outcome of this paper provides robust practical implication for LSS researchers and practitioners. The researcher and practitioners must consciously concentrate on the identified LSSBs more conventionally during LSS implementation, and they need to plan strategically to avoid any implementation failure. Originality/value: For successful implementation of LSS in any organization, it is necessary and permeable to make strategy for controlling LSS barriers at initial stage. So this paper is a leading attempt to highlight main LSS barriers and interrelate them using ISM and MICMAC approach. It provides a clear path for tackling LSS barriers to engineering managers, researchers and consultants.